Employing kübler-ross’ model of change management to explore and interpret ’Habibie & Ainun’ film and beyond and its implication on leading and managing organizational change - Dela Jaskara; Iman Permana (President University, 2022)
There are limited studies that use analysis of film as the key resource of management study. This paper examines Kübler-Ross’ five stages of grief model through the story of a feature film titled Habibie & Ainun. This paper describes the emotional responses exhibited by Habibie, the main character in Habibie & Ainun affected by the shocking change, analyzes these responses using the Kübler-Ross stages of grief, and assesses the usefulness of the Kübler-Ross stages of grief model for understanding any changes in life, including its implication on leading and managing organizational change. Explorative and interpretative study in qualitative research approach. Content analysis will be used as a method of analysis. The study used the Five-Stages Model of Grief, introduced by Elisabeth Kübler-Ross, to analyze how the character of Mr. B.J. Habibie (BJH), as portrayed in the film, transitioned through his grief from analysis of the narrative, scenes within the film, and recorded interviews in a talk show (Mata Najwa & Indonesia Satu). Later they were classified into the theoretical framework of Kübler-Ross's five stages of grief model. This analysis results demonstrated that the grieving process of BJH after the loss of Ibu Ainun could be used to be a learning experience of grief based on the Kübler-Ross grief model, encouraging reflection and critical assessment on the subject, which contributes to a better understanding of our self and our surrounding during the grieving period due to any significant changes in life and how it implies on leading and managing organizational change.